Clinical analysis of cervical intraepithelial neoplasia with vaginal intraepithelial neoplasia. Issue 17 (April 2017) - He, Yue; Zhao, Qun; Geng, Yu-Ning; Yang, Shu-Li; Yin, Cheng-Hong; Wu, Yu-Mei
Abstract : Abstract: The purpose of this prospective cohort study is to evaluate the importance of screening and its diagnostic accuracy compared with the pathological diagnosis of cervical intraepithelial neoplasia (CIN) with vaginal intraepithelial neoplasia (VAIN). The prospective study enrolled 419 patients (pts) and was conducted between February 1, 2015 and January 31, 2016 at Beijing Obstetrics and Gynecology Hospital, Capital Medical University. All enrolled pts underwent multipoint biopsy of cervix and vaginal wall directed by colposcopy. All samples of biopsy underwent pathological examination. Among them, 201 pts (48.0%) were diagnosed with CIN, 218 pts (52.0%) were diagnosed with cervicitis, and 51 pts (12.2%) were diagnosed with VAIN. It was found that the incidence of CIN in pts was 4 times higher than that of VAIN. In all 419 patients enrolled, 218 pts had cervicitis with 13 pts (6.0%) of VAIN. There were 201 pts of CIN with 38 pts (18.9%) of VAIN: including 53 pts of CIN3 with 12 pts (22.6%) of VAIN; 49 pts of CIN2 with 9 pts of VAIN (18.4%), and 99 pts of CIN1 with 17 pts of VAIN (17.2%). The incidence of CIN with VAIN (18.9%) was significantly higher than cervicitis with VAIN (6.0%) ( χ 2 = 16.39, P = .00). Our results showed that there was a significant consistency between cervical lesions and vaginal lesions ( χ 2 = 135.91, P = .00), which indicated that the increase of CIN grades may be related to an increase of the VAIN grades. Our results also showed the significant ( p < .05) increase of CIN and VAIN with age (<40 years Kappa = 0.04; 40–50 years Kappa = 0.11; >50 years Kappa = 0.28). This study showed that cytological test can be used as a routine screening method for cervical lesions and vaginal diseases. If the cytology result shows abnormality, and pathological examination confirms that there is no obvious abnormal cervical disease, colposcopy directed vaginal multipoint biopsy should be conducted to exclude vaginal disease. All patients of CIN should routinely undergo vaginal multipoint biopsy (1/3 upper vagina), especially in patients with high-grade CIN and age older than 50 years.